(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article deals with the «cultural code» concept and clarifies features representing cultural codes, fixed in Ukrainian paralinguistic phraseology. It reviews ethnocodes system of Ukrainian culture, which correlates to the phraseology images, mostly based on the component structure of set expressions.